Pengabdian Kepada Masyarakat: Pelatihan Bahasa Inggris Untuk Meningkatkan Keterampilan Komunikasi Mahasiswa Institut Kesehatan Dan Bisnis St. Fatimah Mamuju - Ariawati Susiandari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
English language proficiency is an important competency for students, especially in the fields of health and business, in facing the challenges of globalization and the world of work. Students at the ST Fatimah Mamuju Institute of Health and Business still face limitations in their English communication skills, especially in terms of speaking and confidence. This Community Service activity aims to improve students' English communication skills through practice-based communicative training. The implementation methods include counseling, training in basic vocabulary and expressions, conversation practice, academic and professional communication simulations, and evaluation through pre-tests and post-tests. The results of the activity show an increase in students' speaking skills, confidence, and active participation in English communication. This activity is expected to improve students' readiness to face the academic and professional world.